Physicochemical Characterization of Simulated Welding Fume from a Spark Discharge System - Park, Jae Hong (Aerosol science and technology : the journal of the American Association for Aerosol Research, 2014)
This study introduces spark discharge system (SDS) as a way to simulate welding fumes. The SDS was developed using welding rods as electrodes with an optional coagulation chamber. The size, morphology, composition, and concentration of the fume produced and the concentration of ozone (O3) and nitrogen oxides (NOX) were characterized. The number median diameter (NMD) and total number concentration (TNC) of fresh fume particles were ranged 10-23 nm and 3.1×107-6×107 particles/cm3, respectively. For fresh fume particles, the total mass concentration (TMC) measured gravimetrically ranged 85-760 μg/m3. The size distribution was stable over a period of 12 h. The NMD and TNC of aged fume particles were ranged 81-154 nm and 1.5×106-2.7×106 particles/cm3, respectively. The composition of the aged fume particles was dominated by Fe and O with an estimated stoichiometry between that of Fe2O3 and Fe3O4. Concentrations of O3 and NOX were ranged 0.07-2.2 ppm and 1-20 ppm, respectively. These results indicate that the SDS is capable of producing stable fumes over a long-period that are similar to actual welding fumes. This system may be useful in toxicological studies and evaluation of instrumentation